Places and non-places in Monica Ali’s Brick Lane - Sereno, Julia Goulart (Palimpsesto - Revista do Programa de Pós-Graduação em Letras da UERJ, 2018)
This article aims at analyzing the role of flashbacks experienced by Nazneen, who is the protagonist of the novel Brick Lane (2003), by Monica Ali. By considering the concepts of spaces, places and non-places proposed by anthropologist Marc Augé in Non-Places: Introduction to an Anthropology of Supermodernity (1994), which is mentioned by phi-losopher Zygmunt Bauman in Liquid Modernity (2000), the present article will demon-strate how Nazneen tries to reconstruct/rewrite her spatial and temporal displacement through her memory. However, what could be seen as an escape is, in essence, a journey in search for meaning, for belonging.